2022
DOI: 10.3390/horticulturae8040316
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on Delignification and Heavy Metals Uptake by Shiitake (Lentinula edodes) Mushroom Cultivated on Agro-Industrial Wastes

Abstract: This study investigates the sustainable production of Shiitake (Lentinula edodes) mushroom using agro-industrial wastes. The substrate of Shiitake (80% rice straw + 20% sugar cane bagasse) was moistened with 0 (freshwater as control), 50, and 100% concentrations of secondarily treated dairy plant and sugar mill wastewaters (DPW and SMW). After proper sterilization, the cultivation was carried out under controlled environmental conditions using the bag log method for 100 days. The results revealed that DPW and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 65 publications
1
12
0
1
Order By: Relevance
“…Most studies indicated that the efficiency of mushroom production is closely related to the nutritional composition of the growing substrate [19,02] and the type of supplement added [9]. The results of our study are in line with the findings of [21,22], who found that adding any amount of additive to the substrate showed an improvement in the quality and yield of mushrooms. (Fig.…”
Section: Fruiting Stagesupporting
confidence: 90%
“…Most studies indicated that the efficiency of mushroom production is closely related to the nutritional composition of the growing substrate [19,02] and the type of supplement added [9]. The results of our study are in line with the findings of [21,22], who found that adding any amount of additive to the substrate showed an improvement in the quality and yield of mushrooms. (Fig.…”
Section: Fruiting Stagesupporting
confidence: 90%
“…Whereas, only a little increase was observed in India as the consumption of mushrooms recently faced with a lack of appetite in some local areas due to its strangeness to traditional cuisine [ 5 ]. Despite this local behavior, this consumption is becoming trendier among youths due to the increasing awareness vis-à-vis its health benefits and low-cost production, as tremendous amounts of raw material based on agro-industrial wastes could be easily found [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mushroom development of P. eryngii can be divided into three stages: hyphal knot, primordium, and fruiting body [ 6 ]. In the three phases, some cultivation environmental factors, such as temperature, light, CO 2, and humidity, could affect the growth and development of fungus [ 7 , 8 ]. Due to the complex genetics and long life cycle of edible fungi, their growth and development are jointly regulated by internal genes and the external environment.…”
Section: Introductionmentioning
confidence: 99%